2020
DOI: 10.28940/terra.v38i3.648
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del efecto de las levaduras vitivinícolas biofungicidas sobre la germinación de semillas y crecimiento de plántulas de lechugas (Lactuca sativa L.) in vitro. Análisis de fitotoxicidad

Abstract: Botrytis cinerea puede afectar a la lechuga tanto en condiciones de invernadero como en condiciones de campo. Levaduras vitivinícolas presentaron actividad antifúngica frente a B. cinerea de lechuga in vitro. Sin embargo se desconoce si estas levaduras afectan la germinación de semillas o crecimiento de las plántulas de lechuga. Objetivo: Evaluar el efecto de las levaduras vitivinícolas sobre la germinación de semillas y crecimiento de plántulas emergentes de lechuga (L. sativa), in vitro. Las levaduras se ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Figure 3 shows the phenology of P. vulgaris with endophytic yeasts individually or in consortium with X. autotrophicus and 70% NH 4 NO 3 compared to non-inoculated P. vulgaris fed with 100% NH 4 NO 3 . There it was evident that in all cases the endophytic yeasts invaded the root system of P. vulgaris with or without X. autotrophicus utilized organic compounds from root metabolism to convert them into various phytohormones 16,17 according to the aerial part of P. vulgaris with higher number of leaves and evident chlorophyll induction 25,21,19 that was higher than in non-inoculated P. vulgaris fed with 100% NH 4 NO 3 according to 70% NH 4 NO 3 concentration. 20,4 A similar positive response was observed in the dense and abundant root system of P. vulgaris treated with endophytic yeasts and X. autotrophicus due to the conversion of root metabolites into several phytohormones, so that despite reducing NH 4 NO 3 to 70% its effective uptake without compromising the healthy growth of P. vulgaris to avoid the generation of greenhouse gases causing global warming, compared to non-inoculated P. vulgaris fed with 100% NH 4 NO 3 , that obviously the legume does not take advantage of P. vulgaris, to avoid the generation of greenhouse gases causing global warming, compared to non-inoculated P. vulgaris fed with 100% NH 4 NO 3 , that obviously the legume does not take advantage of, according to what was observed in aerial and root growth, consequently, this remnant contributes to the release of greenhouse gases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 3 shows the phenology of P. vulgaris with endophytic yeasts individually or in consortium with X. autotrophicus and 70% NH 4 NO 3 compared to non-inoculated P. vulgaris fed with 100% NH 4 NO 3 . There it was evident that in all cases the endophytic yeasts invaded the root system of P. vulgaris with or without X. autotrophicus utilized organic compounds from root metabolism to convert them into various phytohormones 16,17 according to the aerial part of P. vulgaris with higher number of leaves and evident chlorophyll induction 25,21,19 that was higher than in non-inoculated P. vulgaris fed with 100% NH 4 NO 3 according to 70% NH 4 NO 3 concentration. 20,4 A similar positive response was observed in the dense and abundant root system of P. vulgaris treated with endophytic yeasts and X. autotrophicus due to the conversion of root metabolites into several phytohormones, so that despite reducing NH 4 NO 3 to 70% its effective uptake without compromising the healthy growth of P. vulgaris to avoid the generation of greenhouse gases causing global warming, compared to non-inoculated P. vulgaris fed with 100% NH 4 NO 3 , that obviously the legume does not take advantage of P. vulgaris, to avoid the generation of greenhouse gases causing global warming, compared to non-inoculated P. vulgaris fed with 100% NH 4 NO 3 , that obviously the legume does not take advantage of, according to what was observed in aerial and root growth, consequently, this remnant contributes to the release of greenhouse gases.…”
Section: Discussionmentioning
confidence: 94%
“…This corroborates the research by Tawfiq et al, 2018, whom reported that S. cervesiae was capable of synthesizing phythormones. Lencinas et al, 19 analyzed S. cerevisiae and S. pombe in Lactuca sativa seeds, reported an increase in germination per centage. The results of the positive effect of S. cervesiae and X. autotrophicus in the P. vulgaris seed, fed NH 4 NO 3 at 70% had a statistical difference, compared to 70.7% germination and that emerged 5 days after the sowing of P. vulgaris, non-inoculated fed with 100% NH 4 NO 3 or relative control (RC).…”
Section: Discussionmentioning
confidence: 99%